LITERATURE AS A PEDAGOGICAL STRATEGY FOR TEACHING THE SPANISH LANGUAGE IN PUBLIC SCHOOLS - Paes de Sá, Jéssica; Sabino da Silva, Grecinildo (Revista Gênero e Interdisciplinaridade, 2023)
The teaching of the Spanish language in public schools over the years has been presenting divergences, as the literature shows itself as a pedagogical proposal for the teaching of Spanish classes, aiming to promote the student to learn a new language, as well as how the application in the classroom allows the student to create ideas and values that, based on the language and the contact with the teacher, can promote the breadth of different literary genres and cultural plurality.